Territorial Disputes in International Arbitration Practice - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
This paper deals with the issue of territorial disputes settlement in international arbitrations. The arbitration represents an efficient way of determining state borders, together with diplomatic means of dispute resolution and procedure before the International Court of Justice. Parties in а dispute choose arbiters, rules of procedure and commit themselves to accept and implement arbitration award, which is based on international law. States can create an ad hoc tribunal or they can decide to resolve the dispute before the Permanent Court of Arbitration in The Hague. In arbitration practice there were cases of successful arbitrations, especially in situations when a dispute was primarily factual and when major economic and political interests were not involved.